Study of platinum impurity atom state in vitreous arsenic selenide - Bordovsky, G.A.; Ali, Hapipah Mohd; Terukov, E.I.; Seregin, P.P.; Rabchanova, T.Y.; Marchenko, A.V. (2012)
Platinum atoms in the structure of As2Se3 glass are stabilized in the form of Pt2+ and Pt4+ ions and correspond to ionized states of the amphoteric two-electron center with negative correlation energy (Pt2+ is an ionized acceptor, and Pt4+ is an ionized donor), whereas the neutral state of the Pt3+ center appears to be unstable.